Two approaches to the solution of the unidimensional inverse problem of thermal quality control - Vavilov V. P. Vladimir Platonovich (1989, 1989)
Two methods are suggested of solving the inverse problem of thermal control. The first method is based on an approximation of the dependences of the useful signal on the thickness and depth of occurrence of flaws; in the unidimensional problem it ensures a defectometric error of 5-30%. The second method is based on the exact solution of the inverse problem by means of its regularization, and it is characterized by an error of 0.3-10%.